A randomized, placebo-controlled trial of zinc supplementation during pregnancy for the prevention of stunting: analysis of maternal serum zinc, cord blood osteocalcin and neonatal birth length - Lili Rohmawati; Dina Keumala Sari; Makmur Sitepu; Kusnandi Rusmil (Medicinski glasnik, 2021)
Aim: To investigate the influence of zinc supplementation on pregnant women for the prevention of stunting through an analysis of maternal serum zinc, cord blood osteocalcin and neonatal birth length. Methods: This study was conducted with pre-test/post-test control groups and double-blind randomization. Patients were pregnant mothers in second or third trimester and with their newborns who met the inclusion criteria. A total of 71 pregnant mothers and their newborns completed this study. They were divided into two groups of 35 and 36 patients, the supplementation (20 mg/day) and placebo groups, respectively for 12 weeks. The parameters assessed were maternal serum zinc levels, cord blood osteocalcin and birth length measurements. Results: The mean maternal serum zinc level was 54.6±8.7 µg/dL from 71 patients. The mean maternal serum zinc levels after zinc supplementation were significantly higher than those of the placebo group: 55.1±9.9 to 59.1±8.6) ?g/dL (p=0.017) and 54.2±7.5 to 50±8.6 ?g/dL (p=0.001), respectively. The comparison of mean cord blood osteocalcin levels and median neonatal birth lengths in the supplementation group was higher than in the placebo group: 131.8±35.3 vs 90.6±35.4 ng/ml (p=0.001) and 49.3 (46.5-51.3) vs 48.3 (46-50.8) cm (p=0.004), respectively. Maternal serum zinc levels after zinc supplementation had a positive significant correlation with cord blood osteocalcin and neonatal birth length: r=0.434 (p=0.001) and r=0.597 (p=0.001), respectively. Conclusion: There was a significant correlation of maternal serum zinc with cord blood osteocalcin and neonatal birth length after zinc supplementation.
Keywords: bone growth; micronutrients; pregnant; pre-post test design